Association between obesity with low muscle mass and dialysis mortality - Wu, Hung‐Chieh; Tseng, Shih‐Fen; Wang, Wei‐Jie; Chen, Hsin‐Jen; Lee, Lin‐Chien (Internal medicine journal, 2017)
Background/Aim To examine the association between body composition and dialysis mortality. Methods Adult patients who underwent haemodialysis in Taoyuan General Hospital from 2012 to 2016 were enrolled. We reviewed their baseline characteristics and followed up their treatment over 5 years after dialysis. Patients with body mass index >25 kg/m2 were defined as obese. High or low muscle mass were classified by skeletal muscle mass index (SMMI) based on consensus from Chinese population. All age‐matched subjects were classified into four groups: (A) optimal; (B) obesity; (C) low muscle mass; and (D) obesity with low muscle mass. Adjusted hazard ratios for mortality and cumulative survival curves were evaluated by Cox proportional hazard model and Kaplan–Meier method. The discriminative power of SMMI was calculated according to the area under the curve and the receiver operating characteristic curve. Results From a total of 176 age‐matched patients, the incidence rates of mortality for different groups were 3.7, 7.8, 10.3 and 16.5 per 1000 person‐months. After adjusting for continuous variables, SMMI was independently associated with mortality. The difference between groups A and D was more significant in women than in men after multivariate adjustment (adjusted hazard ratios: 7.465 vs 1.682) (P = 0.035 and 0.553). The discriminative power of SMMI to predict 5‐year mortality was 0.700 for men and 0.750 for women, and the best cut‐off values were 11.1 and 8.4 kg/m2 Conclusions Low muscle mass was associated with dialysis mortality. Obesity with low muscle mass was a predictor for dialysis mortality in women.